Development of e-pocket book learning media on environmental pollution based on environmental issues in Cirebon region - Ina Rosdiana Lesmanawati; Shofwatun Nada; Siti Nur'aisyah (University of Muhammadiyah Malang, 2024)
In the Cirebon region, there are several environmental issues exists, one of the problems is pollution. In the context of modern information technology, there's a growing preference for electronic-based educational materials. This study aims to evaluate the environmental pollution levels in Cirebon and develop a e-pocket book as a biology learning resource for high school students. The research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and utilizes observations, questionnaires, and documentation for data collection. The environmental assessment was conducted in Cirebon city and regency, and the learning media developed at MAN 2 Cirebon City. Results from the Environmental Quality Index (IKLH) indicate moderate pollution levels in Kejaksan District and mild-moderate levels in Talun District. The e-book was created using the Canva application and finalized into a link format compatible with laptops and Android smartphones. It underwent validation by material experts, media experts, biology educators, and student users, receiving favorable feedback with an overall rating of 87.24% deemed very satisfactory. It can be concluded that the development of this e-book on environmental pollution can be used as a learning media.